Mahmudkhoja Behbudiy's Approach to Bekhbudiyi's Cultural Autonomy Project of Turkey and the Political Governance Policy - Mukhtarov Sardorbek Saydullo ogli; Gayratova Gulzoda San'atbek qizi; Mamajonova Gulmira Dilbek qizi (Research Parks Publishing LLC, 2020)
In this article, we have tried to cover the project of Mahmudhoja Behbudi and himself, which he called